PENGUATAN PEMAHAMAN SIFAT 20 MENURUT AL-QUR`AN DI SD AL-AZHAR SYIFA, CIBINONG - Nur Rofiah; Puput Sihabudin; Nur Afif; Ulfa Mina Azkiya; A Juraidi (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
In understanding the nature of 20 Nahdlatul Ulama and Muhammadiyah have different views even though the founder of Nahdlatul Ulama Hasyim Asy'ari and the founder of Muhammadiyah Ahmad Dahlan have the same teacher, namely Kiyai Shaleh Darat, but they both have different understandings in terms of branch or furu' worship.Compulsory the Characteristic of 20 according to Nahdlatul Ulama does not limit the majesty and perfection of Allah without limits. Precisely the 20 obligatory attributes are the basic characteristics of the perfection of Allah subhanahu wata'âlâ which are unlimited in number, human reason cannot reach to discuss the Majesty and Perfection of Allah, but the inability to know the characteristics that are not explained by the propositions of 'aqli and naqli makes humans not get punished for it, thanks to the grace of Allah subhânahu wata'âlâ.The characteristic of 20 according to Muhammadiyah, the points of monotheism guided by Muhammadiyah are similar to the concept of 13 or 20 obligatory attributes for Allah, typical of Asy'ariyah. However, with the note that Muhammadiyah avoids talking about things that cannot be understood by reason, so it is enough to think about His creatures to prove His power and wisdom. Muhammadiyah also considers that the nature of Allah subhânahu wata'âlâ is unlimited, because Allah is Absolute without any limitations.This research is motivated by the phenomenon of differences of opinion in the community regarding the characteristic of 20 due to mutual blame between one another. This research is intended to present the issue of the characteristic of 20 in the Qur'an according to the views of Nahdlatul Ulama and Muhammadiyah, as well as a comparative analysis between Nahdlatul Ulama and Muhammadiyah by finding points of similarities and differences in views in understanding the characteristic of 20 which is based on the Qur'an. This thesis will also discuss the history behind the founding of Nahdlatul Ulama and Muhammadiyah and their contribution to the Unitary State of the Republic of Indonesia.This type of research is qualitative research thematic studies, with a library research approach that collects data related to the title and discussion in this thesis